102. Effects of an Antimicrobial Stewardship-guided MRSA Nasal Screening Review on Vancomycin Utilization for Respiratory Infections: A Quasi-Experimental Study. (31st December 2020) - Pineda, Ross; Kanatani, Meganne; Deville, Jaime
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) remains a significant pathogen in patients with respiratory infections. Guidelines recommend empiric MRSA coverage in patients at increased risk, resulting in substantial vancomycin use. Recent literature highlights the use of MRSA nasal assays as a rapid screening tool for MRSA pneumonia, demonstrating high negative predictive values and allowing for shorter empiric coverage. We aimed to evaluate the impact of MRSA nasal screening review by the antimicrobial stewardship program (ASP) on vancomycin utilization for respiratory infections. Methods: This was a retrospective, quasi-experimental, pre-post intervention study. The intervention saw the addition of an MRSA screening review tool into the ASP electronic record, highlighting patients on vancomycin (actively or recently administered) with a negative MRSA screening. Vancomycin days of therapy (DOT) was collected for all orders indicated for a respiratory infection in the two weeks following a negative screening. Additional outcomes include vancomycin total dose and DOT per 1, 000 patient days. Outcomes were compared via independent samples t-tests. Results: 1, 110 MRSA screenings resulted across 2 months, of which the majority were excluded for either not having vancomycin ordered, or for having vancomycin ordered for a non-respiratory indication, leaving 37 and 35 evaluable screenings in the pre- and post-intervention groups, respectively. Regarding vancomycin DOT, we did not identify a significant difference between pre- and post-intervention groups with respective means of 2.45 (SD=1.52) and 2.14 (SD=1.12) (p=0.35). We identified a total 8.78 vancomycin DOT per 1, 000 patient days in the pre-intervention group versus 6.69 in the post-intervention group. Conclusion: ASP-guided review of MRSA screenings was associated with a nonsignificant decrease in mean vancomycin DOT and lower total DOT per 1, 000 patient days for respiratory infections following a negative screen. Given the recent implementation of our intervention, our analysis covered a small sample size, highlighting the need for continued data collection. MRSA screenings are not always fully or immediately utilized in our institution, demonstrating room to de-escalate MRSA-targeted antibiotics. Disclosures: All Authors : No reported disclosures